Attack of the ninja frogs - Vernon, Ursula (Vernon, Ursula. Dragonbreath, 2010)
When Suki the salamander--the new foreign exchange student--is being stalked by ninja frogs, Danny, Wendell the iguana, and Suki travel to Great-grandfather Dragonbreath's home in mythical Japan to find a solution for the problem.